2019
DOI: 10.26803/ijlter.18.9.13
|View full text |Cite
|
Sign up to set email alerts
|

Transition from Educational Leadership to e-Leadership: A Data Analysis Report from TEI of Western Greece

Abstract: negative correlation with passive -to avoid leadership, it was confirmed that the higher degree of transformational leadership implies greater efficiency and satisfaction for workers, and the high degree of transformational leadership co-exists with the great degree of implementation of digital leadership.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 13 publications
0
26
0
1
Order By: Relevance
“…Also, the high number of declared digital properties showed high levels of efficiency and satisfaction from leadership training [19]. In addition, in recent research, leadership outcome seems to have a positive and statistically significant effect (p = 0.014) on digital leadership, that is, the greater the effectiveness and satisfaction of the leadership, the greater the degree of Digital leadership practice [20].…”
Section: -5-digital Leadershipmentioning
confidence: 90%
“…Also, the high number of declared digital properties showed high levels of efficiency and satisfaction from leadership training [19]. In addition, in recent research, leadership outcome seems to have a positive and statistically significant effect (p = 0.014) on digital leadership, that is, the greater the effectiveness and satisfaction of the leadership, the greater the degree of Digital leadership practice [20].…”
Section: -5-digital Leadershipmentioning
confidence: 90%
“…On the other hand, both Transactional and Passive Leadership seem to have no statistically meaningful effect on the degree of Digital Leadership [38]. Additionally, the high number of declared digital assets indicated that leadership training generated high productivity and satisfaction levels [39]. Additionally, recent research indicates that leadership outcome has a favorable and statistically significant impact (p = 0.014) on digital leadership, implying that the more successful and satisfied the leader, the greater the degree of digital leadership experience [40].…”
Section: -6-digital Leadershipmentioning
confidence: 98%
“…In allen fünf Dimensionen der Schulentwicklung mit digitalen Medien (u. a. Schulz-Zander, 2001) kommt Schulleitungen dabei eine Schlüsselrolle zu (vgl. Eickelmann & Gerick, 2017 (Antonopoulou, Halkiopoulos, Barlou & Beligiannis, 2019;Chua & Chua, 2017;Davies, 2010). Nicht ausreichend geklärt erscheint bisher jedoch, in welchen (Schulmanagement-)Bereichen digitale Medien derzeit genutzt werden und mit welchen Potenzialen, Veränderungen und Herausforderungen dies verbunden ist.…”
Section: Th Eorie Und Forschungsstandunclassified